2022
DOI: 10.1111/fare.12694
|View full text |Cite
|
Sign up to set email alerts
|

“Cardiotoxic” and “cardioprotective” partner support for patient activation and distress: Are two better than one?

Abstract: The study aimed to test whether the presence of a partner was always beneficial to people with cardiac disease and how different types of partner behaviors promoted or hindered their activation and distress. Background: Cardiac disease challenges not only patients but also their partners, whose support is not always effective. Method: A cross-sectional dyadic research design, in which both partners completed a self-report questionnaire during hospitalization, was adopted. The associations between partner suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Based on our results, we cannot answer the question of whether overprotection is maladaptive in the context of fear of falling and increases loss of independence in old age. Cross-sectional studies suggest that overprotection of the social environment is significantly related to lower levels of activation (Bertoni et al, 2022;Sánchez-Garcia et al, 2019). In line with these cross-sectional results, a longitudinal dyadic study on patients surveyed after myocardial infarction revealed that perceiving a partner as overprotective predicted a decline in physical functioning nine months later (Joekes et al, 2007).…”
Section: Future Researchmentioning
confidence: 62%
See 2 more Smart Citations
“…Based on our results, we cannot answer the question of whether overprotection is maladaptive in the context of fear of falling and increases loss of independence in old age. Cross-sectional studies suggest that overprotection of the social environment is significantly related to lower levels of activation (Bertoni et al, 2022;Sánchez-Garcia et al, 2019). In line with these cross-sectional results, a longitudinal dyadic study on patients surveyed after myocardial infarction revealed that perceiving a partner as overprotective predicted a decline in physical functioning nine months later (Joekes et al, 2007).…”
Section: Future Researchmentioning
confidence: 62%
“…In a qualitative study by Gallant et al (2007), older adults reported discouragement of physical activity as one example of overprotection. Quantitative research extended this finding and revealed that overprotection is related to lower levels of activation and predicts a decline in physical functioning in the long term (Bertoni et al, 2022;Joekes et al, 2007).…”
Section: Fear Of Falling Carries Over Into Social Exchange Processes ...mentioning
confidence: 74%
See 1 more Smart Citation
“…Fourth, even though patient activation primarily focusses on behaviour change through having confidence to take action to maintain one's health compared with health literacy, there may be overlapping features such as knowledge and skills regarding managing one's own health care (Hibbard, 2017 ; Huang et al, 2021 ). Lastly, partner presence may play a statiscally significant role in encouraging patient activation for HF self‐care in older population (Berton et al, 2022 ). However, this study only focussed on patient's individual aspects.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, patients who feel poorly emotionally supported experience a 41% higher risk of non-compliance with the treatment than those who feel supported by their partner (Leifheit-Limson et al, 2012). Furthermore, perceiving the partner as hostile or overprotective could hinder the patients' motivation or become a barrier to behavioral changes, thus affecting their health (Fiske et al, 1991;Rapelli et al, 2020b;Bertoni et al, 2022).…”
Section: Introductionmentioning
confidence: 99%